2020
DOI: 10.29252/mlj.14.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of Selenium and Risk of Esophageal Cancer: A Review

Abstract: Esophageal cancer (EC) is one of the most common types of cancer, especially in Asia. Esophageal squamous cell cancer (ESCC) is the most important histological subtype of EC, which accounts for 90% of all EC cases worldwide. ESCC is highly prevalent in Turkey, Iran, Kazakhstan and northern and central parts of China. Selenium is an essential micronutrient that is required for cellular functioning and synthesis of several selenoproteins. It also modulates the antioxidant defense system, cell cycle and apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 103 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Selenium functions as an anti-oxidant and plays a possible chemo-preventive role against cancer through scavenging reactive oxygen species (ROS), thereby preventing damage to the DNA and occurrence of mutations [ 34 ]. The effects of selenium status on cancer were studied in several clinical trials and epidemiologic studies in humans, suggesting the beneficial effects of higher selenium status in preventing the recurrence of lung cancer [ 35 ] and patients with different cancer types [ 11 ]. We thus hypothesized that selenium might reduce ROS production and DNA damage against ESSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium functions as an anti-oxidant and plays a possible chemo-preventive role against cancer through scavenging reactive oxygen species (ROS), thereby preventing damage to the DNA and occurrence of mutations [ 34 ]. The effects of selenium status on cancer were studied in several clinical trials and epidemiologic studies in humans, suggesting the beneficial effects of higher selenium status in preventing the recurrence of lung cancer [ 35 ] and patients with different cancer types [ 11 ]. We thus hypothesized that selenium might reduce ROS production and DNA damage against ESSC.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se) is a vital and unique trace element that helps to prevent various tumor malignancies, including ESCC [ 10 , 11 ]. Previous studies described a significant inverse correlation between serum selenium levels and the risk of ESCC in China’s high-risk areas [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between older age and COVID-19 mortality can be due to age-related dysfunction in T lymphocyte and B lymphocyte and increased type 2 cytokines production, which leads to impaired control of virus replication and ultimately leads to poor outcome [ 25 ]. Selenium is an essential trace element that exerts its main function on the health of the body through selenocysteine in the structure of selenoproteins [ 26 , 27 ]. Adequate levels of selenium are essential for central nervous system function, male reproduction, endocrine system, muscle function, cardiovascular system, and immune system [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that high levels of selenium in this area may play a possible role in EC pathogenesis. 25,26,27,28 The case-control study nested within the Golestan Cohort reported that toenail selenium concentrations did not differ significantly between cases of ESSC in highrisk areas and healthy subjects, and there was no association between toenail selenium concentrations and the ESCC risk in this population. 29 Another study in Golestan province showed that in the high-risk areas of EC, the association between selenium and the risk of developing ESSC was non-linear and U-shaped.…”
Section: Discussionmentioning
confidence: 95%